Transverse Sinus Stenting for Idiopathic Intracranial Hypertension: A Review of 52 Patients and of Model Predictions - Ahmed, R.M.; Wilkinson, M.; Parker, G.D.; Thurtell, M.J.; Macdonald, J.; McCluskey, P.J.; Allan, R.; Dunne, V.; Hanlon, M.; Owler, B.K.; Halmagyi, G.M. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Transverse sinus stenosis is common in patients with IIH. While the role of transverse sinus stenosis in IIH pathogenesis remains controversial, modeling studies suggest that stent placement within a transverse sinus stenosis with a significant pressure gradient should decrease cerebral venous pressure, improve CSF resorption in the venous system, and thereby reduce intracranial (CSF) pressure, improving the symptoms of IIH and reducing papilledema. We aimed to determine if IIH could be reliably treated by stent placement in transverse sinus stenosis. MATERIALS AND METHODS: We reviewed the clinical, venographic, and intracranial pressure data before and after stent placement in transverse sinus stenosis in 52 of our own patients with IIH unresponsive to maximum acceptable medical treatment, treated since 2001 and followed between 2 months and 9 years. RESULTS: Before stent placement, the mean superior sagittal sinus pressure was 34 mm Hg (462 mm H20) with a mean transverse sinus stenosis gradient of 20 mm Hg. The mean lumbar CSF pressure before stent placement was 322 mm H2O. In all 52 patients, stent placement immediately eliminated the TSS pressure gradient, rapidly improved IIH symptoms, and abolished papilledema. In 6 patients, symptom relapse (headache) was associated with increased venous pressure and recurrent stenosis adjacent to the previous stent. In these cases, placement of another stent again removed the transverse sinus stenosis pressure gradient and improved symptoms. Of the 52 patients, 49 have been cured of all IIH symptoms. CONCLUSIONS: These findings indicate a role for transverse sinus stent placement in the management of selected patients with IIH. ATECOautotriggered elliptic centric-orderedIIHidiopathic intracranial hypertensionLPlumbar punctureMRVMR venographypCO2partial pressure of carbon dioxideTSStransverse sinus stenosis